STUDI KORELASI BAB "YAKIN DAN TAWAKAL" DALAM KITAB "RIYADHUS SHOLIHIN" DENGAN TAUHID ULUHIYAH - Muhammad Nur Ihsan (Al-Majaalis : Jurnal Dirasat Islamiyah, 2020)
The book "RiyadhusSholihin" is a monumental work written by one of the great scholars who had a high reputation among the Muslims, namely Imam Nawawi. Although the main topic of the book is about inspiriting anddishearteningand purification of the self, the book also includes themes of creed and oneness of Allah conceptualized by the author in separate chapters accompanied by the evidences of Qur'an and hadith, including the chapters ofBelief and Reliance. So, how is the correlation between the verses and hadiths that he brought with that chapter and with the tauhid ulooheeyah ‘maintaining the unity of worship’? This simple paper attempts to answer these questions by using a library research method and qualitative research with a content analysis approach.The discussion of this paper is divided into several sub-discussions: introduction, brief biography of Imam Nawawi, the meaning of tauhid ulooheeyah, belief and reliance, and the study of the correlation of the chapter and its arguments with tauhid ulooheeyah, and finally the conclusion, including the followings: (1) The RiyadhusSholihin is not a mere hadith book that discusses the themes of inspiriting anddishearteningand purification of the self, but also contains materials of creed; (2) Imam Nawawi's foresight in conceptualizing the chapters of the book and selecting related evidencesfor them; (3) The correlation of the evidences presented with the Chapter of Belief and Reliance is very clear and close; (4) Belief and reliance have a very close correlation, because reliance is the fruit of belief; (5) The correlation between the chapter Belief and Reliance with tauhid ulooheeyahis very real, because belief and reliance are the foundation of faith and excellence in all acts of worship, their position is like the head of the body.